Nurses' Ability to Detect Problems of Hospital-Acquired Infections the Effects of Risk Factors, Expertise, and Time Pressure. (September 2015) - Gregg, Sarah; Durso, Francis T.
Nurses must manage a variety of problems in order to maintain performance. The first step in managing these problems is detecting that there is in fact a problem. The current study aimed to investigate how nurses detect the problem of a patient developing a hospital-acquired infection (HAI). Specifically, the experiment examined the effects of varying the number of risk factors, nurse experience, and the presence or absence of time pressure. General findings and implications are discussed.